Intracellular Condensates of Oligopeptide for Targeting Lysosome and Addressing Multiple Drug Resistance of Cancer (Adv. Mater. 1/2022). Issue 1 (7th January 2022) - Wang, Jing; Hu, Liangbo; Zhang, Hongyue; Fang, Yu; Wang, Tingliang; Wang, Huaimin
Abstract : Artificial Biomolecular Condensates In article number 2104704, Huaimin Wang and co‐workers report a general approach for constructing artificial biomolecular condensates of oligopeptide in living cells. The rationally designed aromatic‐capped peptides can reversibly form a nanofibrous hydrogel with a change of the conformation and morphologies in the lysosome. The formed condensates undergo swelling in the lysosome, leading to lysosomal membrane permeabilization and re‐direction of therapeutic drugs to the target.